Enhancing Financial Capability Through the Socialization of Sharia Accounting at the Selaras Pinang Masak People’s Craft Center, Jambi - Rafidah, Rafidah; Rahman, Nur Hayati Abd; Elyanti, Elyanti; Nazori, Nazori; Martaliah, Nurfitri; Anita, Efni; Alawiyah, Rabiyatul; Herlambang, Ilham Wisnu; Aminatah, Aminatah (International Journal of Community Service (IJCS), 2025)
This Community Service Program aims to strengthen the financial capabilities of MSME actors at BKR Selaras Pinang Masak through intensive socialization and practical training on Sharia Accounting. The method used involves a comprehensive approach, including a pre-test, in-depth delivery of material on Sharia accounting principles, practice of simple financial recordkeeping, a post-test, and evaluation. The results show a significant improvement in participants’ understanding of Sharia accounting concepts, financial recording accuracy, and awareness of Sharia-compliant financial management. This program successfully provided a foundation for MSMEs to manage their finances more transparently and ethically, improving their eligibility for Sharia-based financing and supporting the sustainability of their businesses. These findings highlight the importance of targeted, appropriate, and practical Sharia Accounting socialization programs in strengthening MSME financial capacity